2014
DOI: 10.1063/1.4865106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the quasi-one-dimensional compounds δ-(EDT-TTF-CONMe2)2X, X=AsF6 and Br by vibrational spectroscopy and density functional theory calculations

Abstract: We have investigated the infrared spectra of the quarter-filled charge-ordered insulators δ-(EDT-TTF-CONMe2)2X (X= AsF6, Br) along all three crystallographic directions in the temperature range from 300 to 10 K. DFT-assisted normal mode analysis of the neutral and ionic EDT-TTF-CONMe2 molecule allows us to assign the experimentally observed intramolecular modes and to obtain relevant information on the charge ordering and intramolecular interactions. From frequencies of charge-sensitive vibrations we deduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Previous work on -Br has shown that it exhibits a charge-ordered Mott insulating state at room temperature and ambient pressure [26,27,28]. Upon cooling, at Ts = 190 K a structural orthorhombic-to-monoclinic phase transition occurs.…”
Section: -(Bedt-mentioning
confidence: 93%
See 4 more Smart Citations
“…Previous work on -Br has shown that it exhibits a charge-ordered Mott insulating state at room temperature and ambient pressure [26,27,28]. Upon cooling, at Ts = 190 K a structural orthorhombic-to-monoclinic phase transition occurs.…”
Section: -(Bedt-mentioning
confidence: 93%
“…These stacks are adjacent along the b axis and separated by Br anions in the c direction, leading to the formation of planes of EDT-TTF-CONMe2 molecules perpendicular to the a axis. Within these planes, a CO pattern was also found along the b direction [26,28]. It should be noted, however, that the interstack distance is significantly larger than the intermolecular distance within a single stack making the material quasi-one-dimensional.…”
Section: -(Bedt-mentioning
confidence: 95%
See 3 more Smart Citations